Fake News in The Alpaquero Textile Business System in Arequipa-Peru During The New Normality - Jara Ortega, Constante Eduardo; Rodríguez, Daniel Eduardo Jara (Archives of Business Research, 2023)
In the COVI-19 pandemic, the dissemination of Fake news increased, increasing in the different business sectors, the alpaca textile sector in Peru, to which the Arequipa Region belongs, considered the second city after Lima, is no stranger to this fact. The present study is of a quantitative level of cross-sectional experimental design, the Fake news that is disseminated in the pandemic and the participation of the alpaca business sector of the Arequipa Region are analyzed, the dimensions of production, sales and consumption in the pandemic were taken into account. of the COVI-19. The survey and the interview have been applied as techniques, the instruments being the questionnaire of questions and the interview questionnaire, this work has been carried out in person using the different institutions and people directly related to the study sector , for which executive personnel of institutions that represent the alpaca textile sector have been considered, concluding that 89% receive false information, the personnel representing and directing associations of the alpaca sector have also been considered, concluding that 99% receive false information , in the analysis of the health area, medical personnel and nurses have been considered participant in the care and treatment of COVI-19, who work for the Ministry of Health, concluding that 90% receive false information.